PENGEMBANGAN PELUANG KEWIRAUSAHAAN JASA KEPARIWISATAAN SEJARAH DAN BUDAYA INDONESIA MELALUI PROGRAM MAGANG KEWIRAUSAHAAN - Rokhnuin, M. Nur (Universitas Negeri Yogyakarta, 2003)
The objectives of this program : (l)To provide the knowledge, skill and experience in the tourism business, theoritically and practically; (2) To provide knC'.